Five Orientations of Indonesian Christian Scholars’ Role: A Reflection Based on Joel A. Carpenter’s Thought - Fery Alexander Pasang (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2021)
Christianity has grown to become the largest of world religions today. One of the strategic roles that Christianity has done so far is the role of its scholars. However, as the direction of its development is moving to the Southern and Eastern hemispheres of the world, Christianity is facing new challenges. The role of the Christian scholars in that area is facing new ones as well. The important question is not how large the extent but how the deep and fruitful Christianity is in the south and the east. In the end, these developments and fruits will have a reverse impact on the world globally. Indonesia is in an area where Christianity is developing and experiencing all these developments. How have Indonesian Christian scholars responded to this? This paper reflects Joel Carpenter's thoughts about Christian scholars' new orientation that the author tries to relate to the Indonesian context. Carpenter’s points of thought are very important and relevant to be implemented seriously in Indonesia. Its implementation becomes a concrete form for Indonesian Christian scholars to carry out their intellectual mandates.